2020
DOI: 10.3390/ijms21020405
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Sensory and Sympathetic Nervous System on Fracture Healing in Ovariectomized Mice

Abstract: The peripheral nervous system modulates bone repair under physiological and pathophysiological conditions. Previously, we reported an essential role for sensory neuropeptide substance P (SP) and sympathetic nerve fibers (SNF) for proper fracture healing and bone structure in a murine tibial fracture model. A similar distortion of bone microarchitecture has been described for mice lacking the sensory neuropeptide α-calcitonin gene-related peptide (α-CGRP). Here, we hypothesize that loss of SP, α-CGRP, and SNF m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 59 publications
0
25
0
Order By: Relevance
“…These findings clearly point towards a neuronal origin of aCGRP-induction during bone regeneration and highlight the importance of sensory innervation of fracture tissue during bone healing. In a recent study by Niedermair et al, it was suggested that aCGRP-deficiency alters M2 macrophage polarization without affecting callus maturation [21]. These divergent findings may be explained by the differences in the fracture model used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings clearly point towards a neuronal origin of aCGRP-induction during bone regeneration and highlight the importance of sensory innervation of fracture tissue during bone healing. In a recent study by Niedermair et al, it was suggested that aCGRP-deficiency alters M2 macrophage polarization without affecting callus maturation [21]. These divergent findings may be explained by the differences in the fracture model used.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, increased in-growth of new nerve fibres containing CGRP at the fracture site have been reported in rats [20] . And finally, although inactivation of CGRP was suggested to alter M2 macrophage polarization without affecting callus maturation in ovariectomized mice [21] , another study demonstrated that magnesium implants promote bone regeneration in rats through CGRP receptor-dependent, osteogenic differentiation of periosteal stem cells [22] .…”
Section: Introductionmentioning
confidence: 99%
“…As an integrated part of the autonomic nervous system of the human body, the sympathetic nervous system serves a key role in regulating homeostasis. Growing evidence has shown that the sympathetic nervous system is involved in bone remodeling (6,35). In 1977, Duncan and Shim (36) demonstrated that the surface of intraosseous vessels is covered with rich adrenergic nerve fibers by observing the bone tissue of rabbits using histochemistry and fluorescence electron microscopy.…”
Section: Discussionmentioning
confidence: 99%
“…As the effects of the sympathetic nervous system on bone remodeling and healing are complex and extensive, the underlying mechanism has not yet been fully recognized (6). Numerous experiments have investigated the effect of propranolol, a sympathetic blocker drug, on bone metabolism (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…As previously mentioned, the periosteum is a critical tissue for bone repair, being a valuable source for regenerative cells, blood vessels for nutrient supply, 81 but also contains sensory neurons. As a source of the neuropeptides substance P and calcitonin gene‐related peptide, sensory neurons appear to play important roles in the bone healing process, 82 and fracture repair in long bones has recently been shown to require nerve growth factor expression in periosteal cells and tropomyosin receptor kinase A signalling in skeletal sensory nerve fibres 83 . Therefore, damage to the periosteum may limit bone healing by interfering with these reparative processes and/or cell populations and should therefore be avoided where at all possible.…”
Section: Preclinical Studies Targeting the Regeneration Of Cmf Bone D...mentioning
confidence: 99%